Clinical and virological profile of locally acquired acute hepatitis E in South Bulgaria - Komitova, Radka; Kevorkyan, Ani; Golkocheva-Markova, Elitsa; Atanasova, Mariya; Rangelova, Vanya; Raycheva, Ralitsa; Ismailova, Chyidem; Stoyanova, Asya; Tenev, Tencho (The Journal of Infection in Developing Countries, 2024)
Introduction: Acute hepatitis E virus (HEV) infection is recognized as a zoonosis in several European countries. We describe the characteristics and outcomes of locally acquired acute HEV hepatitis. Methodology: A prospective study was conducted among adult patients with acute HEV hepatitis at the University Hospital in Plovdiv, South Bulgaria between January 2020 and May 2022. An acute HEV infection case was a patient with acute hepatitis and laboratory-confirmed anti-HEV IgM antibodies and/or HEV RNA in serum. Demographic data, clinical manifestations, laboratory test results, and outcomes were recorded. Results: A total of 46 patients were selected. Median age of 65 years (interquartile range [IQR] 50.8-74.3). 28 (60.87%) were male. 22 (47.83%) had comorbidities such as diabetes (15), liver cirrhosis (3), hepatitis B virus infection (2), and malignancies (2). Of the 46, 18 (39.13%) patients were viremic and, HEV genotype 3 was detected. The median (IQR) serum alanine aminotransferase, aspartate aminotransferase, bilirubin, platelet, and international normalized ratio levels were 992 (495.8-1714.3) U/L, 715 (262.5-1259.3) U/L, 204 (132.3-235.5) µmol/L, 204 (132.3-235.5) ×109 L, and 1.0 (0.89-1.19), respectively. Six patients with underlying liver diseases had severe hepatitis. A young patient with osteoarthritis progressed to acute liver failure and died. The persistent HEV infection was ruled out in 2 malignant patients who tested HEV RNA negative three months after discharge. Conclusions: Acute HEV hepatitis is a diagnosis to consider after excluding other causes of acute viral hepatitis. A diagnostic workup should include timely testing for HEV to identify the most vulnerable to severe consequences.